Nrf2 deficiency exacerbates frailty and sarcopenia by impairing skeletal muscle mitochondrial biogenesis and dynamics in an age-dependent manner - Huang, Dong-Dong; Fan, Sheng-Dong; Chen, Xi-Yi; Yan, Xia-Lin; Zhang, Xian-Zhong; Ma, Bing-Wei; Yu, Ding-Ye; Xiao, Wen-Yu; Zhuang, Cheng-Le; Yu, Zhen (Experimental gerontology, 2019)
Mitochondrial dysfunction during aging is a key factor that contributes to sarcopenia. Nuclear factor erythroid 2-related factor 2 (Nrf2) has been increasingly recognized to regulate mitochondrial function. The present study aimed to investigate the role of Nrf2 in the development of frailty and sarcopenia during aging, and to demonstrate whether Nrf2 contributes to the maintenance of muscle mass and function by regulation of mitochondrial biogenesis and dynamics during the aging process. Young (5–6 months), middle-aged (11-13 months), old (20–24 months) Nrf2−/− (knockout, KO) mice and age-matched wild-type (WT) C57/BL6 mice were used in this study. Physical function of the mice in the 6 groups was assessed by grip strength test, four paw inverted hanging test, rotarod analysis, open field analysis, and treadmill endurance test. Muscle mass was measured by cross-sectional area (CSA) of tibialis anterior muscles and gastrocnemius muscle weight. The frailty status of the 25 old WT mice and 23 old KO mice were assessed based on the mouse frailty phenotype assessment. Expression levels of genes involved in mitochondrial biogenesis (nuclear respiratory factor 1 (Nrf1), peroxisome proliferative activated receptor, gamma, coactivator 1 alpha (PGC-1α), mitochondrial transcription factor A (TFAM)) and mitochondrial dynamics (optic atrophy protein 1 (Opa1), mitofusin 1 (Mfn1), mitofusin 2 (Mfn2), and dynamin-related protein 1 (Drp1)) were measured in the skeletal muscle. SDH staining was performed and mitochondrial DNA (mtDNA) copy number was measured. Transmission electron microscopy was used to measure the mitochondria number and morphology. Physical function and muscle mass decreased during aging. The mRNA expression levels of Nrf2 decreased with increasing frailty phenotype scores in the old WT mice. There were minimal differences in the physical function and muscle mass between the WT and KO mice in the young groups, whereas Nrf2 deficiency caused a declined physical function and muscle mass in the middle-aged and old mice, and exacerbated frailty in the old mice. The decreases of the physical function and muscle mass were accompanied by the reduced expression levels of genes involved in mitochondrial biogenesis and dynamics, as well as a reduction of mitochondrial number, mitochondrial content, mtDNA copy number, and an impaired mitochondria morphology in the skeletal muscle. Nrf2 deficiency exacerbated frailty and sarcopenia during aging, at least partially by impairing skeletal muscle mitochondrial biogenesis and dynamics in an age-dependent manner. •Muscle mass/function and mitochondrial homeostasis are impaired during aging in mice.•Decline of muscle mass/function is linked with mitochondrial dysfunction during aging.•Nrf2 deficiency has few effect on frailty/sarcopenia and mitochondria in young mice.•Nrf2 deficiency worsens mitochondrial dysfunction, frailty/sarcopenia in older mice.